Effectiveness of endodontic solvents: An integrative literature review (Research, Society and Development, 2024)
Endodontic retreatment requires the removal of the filling material to ensure that the root canal is cleaned, allowing periapical health to be restored. Endodontic solvents are commonly used for this purpose. Given the diversity of solvents available on the market with different properties and forms of use, this study aimed to compare, according to their effectiveness, some of the most commonly used endodontic solvents: chloroform, halothane, rectified turpentine, orange oil, eucalyptol, d-limonene, xylene and tetrachlorethylene. A search was carried out in the PubMED/Medline, SciELO, Cochrane Library and Google Scholar databases using the terms "endodontic solvents" and "effectiveness". The studies were selected by title and abstract, with no language and/or publication date filtering. The results regarding the effectiveness of solvents vary greatly in the literature, as the studies are subject to different methods and ways of evaluating the performance of different compounds, such as ambient and compound temperature, form of application, time of action, storage time of the specimens, among others. The use of essential oils such as eucalyptol and orange oil has been growing, as these solvents have good effectiveness and are cited in the literature as safer alternatives to more toxic solvents such as chloroform and xylene. There are several types of solvent and the choice of the best one depends on the case to be treated, considering the harmony between the component's dissolving capacity and the safety of the tissues, the patient and the operator when using the solvent.